Plastid-Nucleus Distance Alters the Behavior of Stromules - Erickson, Jessica L.; Kantek, Matthias; Schattat, Martin H. (Frontiers in Plant Science, 2017)
Plastids send 'retrograde' signals to the nucleus to deliver information regarding their physiological status. One open question concerning this signal transfer is how the signal bridges the cytoplasm. Based on individual reports of plastid derived tubular membrane extensions connecting to nuclei, these so-called stromules have been suggested to function as communication routes between plastids and nuclei in response to biotic stress. However, based on the data currently available it is unclear whether interactions between stromules and nuclei are truly intentional or observed as a result of an inflated stromule frequency throughout the cell, and are thus a random event. The source of this uncertainty stems from missing information regarding the relative distribution of all plastids and stromules within a given cell. A comprehensive analysis of the upper epidermis of Arabidopsis thaliana rosette leaves was performed via a combination of still images and time-lapse movies of stromule formation in the context of the whole cell. This analysis could definitively confirm that stromule formation is not evenly distributed. Stromules are significantly more frequent within 8 µm of the nucleus, and approximately 90% of said stromules formed facing the nucleus. Time-lapse movies revealed that this enrichment of stromules is achieved via a ten fold higher frequency of stromule initiation events within this 8 µm zone compared to the cell periphery. Following the movement of plastids and nuclei it became evident that movement and formation of stromules is correlated to nucleus movement. Observations suggest that stromules ‘connecting’ to the nucleus are not necessarily the result of plastids sensing the nucleus and reaching out towards it, but are rather pulled out of the surface of nucleus associated plastids during opposing movement of these two organelles. This finding does not exclude the possibility that stromules could be transferring signals to the nucleus. However, this work provides support for an alternative hypothesis to explain stromule-nuclear interactions, suggesting that the main purpose of nucleus associated stromules may be to ensure a certain number of plastids maintain contact with the constantly moving nucleus.